In Search of Other Borders: Guatemalan-Mexican Communities in Southern Mexico - CHAN, Lidia Patricia; GARCÍA, Martha (Frontera Norte, 2018)
Accounting 35 years after arriving to Mexico, Guatemalan families with Mayan ethnic origins created a trade type economic niche, connecting agriculture production with market practices, in the Mexican cities of Chetumal and Cancun. With in-detail ethnographic research, this article provides evidence on this population’s three-decade evolution from Guatemalan refugee into communities of Mexican tradesmen developing innovative economic practices. This given transformation may be observed in the context of cultural losses, showing lack of public policy under the Mexican integration aftermath; e.g., loss in the sphere of linguistics.